2012
DOI: 10.1016/j.ypmed.2011.11.014
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 as a therapeutic target in inflammaging of the pulmonary disease

Abstract: Objective Chronic inflammation and cellular senescence are intertwined in the pathogenesis of premature aging, which is considered as an important contributing factor in driving chronic obstructive pulmonary disease (COPD). SIRT1, a NAD+-dependent protein/histone deacetylase, regulates inflammation, senescence/aging, stress resistance, and DNA damage repair via deacetylating intracellular signaling molecules and chromatin histones. The present review describes the mechanism and regulation of SIRT1 by environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 151 publications
(193 reference statements)
0
74
0
2
Order By: Relevance
“…Inflammation and cellular senescence are intertwined in the process of accelerated or premature lung aging (inflammaging) (71). The percentage of proinflammatory senescent type II cells expressing both p16 and phosphorylated NF-κB (i.e., senescence-associated secretory phenotype [SASP]) has been shown to be augmented in lungs of COPD patients compared with smokers and nonsmokers (33).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation and cellular senescence are intertwined in the process of accelerated or premature lung aging (inflammaging) (71). The percentage of proinflammatory senescent type II cells expressing both p16 and phosphorylated NF-κB (i.e., senescence-associated secretory phenotype [SASP]) has been shown to be augmented in lungs of COPD patients compared with smokers and nonsmokers (33).…”
Section: Figurementioning
confidence: 99%
“…These findings highlight the mechanism of SIPS in the pathogenesis of COPD/emphysema. They also provide the rationale for a key and specific therapeutic target via pharmacological activation of SIRT1 in ameliorating/halting the progression of this diverse and complex debilitating disease (71,77). Hence, the activation of SIRT1 may prove a therapeutic intervention to prevent premature lung senescence/aging in COPD.…”
Section: Figurementioning
confidence: 99%
“…Targeted disruption of FOXO3 results in downregulation of these antioxidant genes in mouse lungs and increases the susceptibility for the development of COPD/emphysema (55). Yao and colleagues have shown that the SIRT1-FOXO3-mediated pathway is important in pathogenesis of COPD independent of the NF-jB pathway (116,184). Further studies on the SIRT1-FOXO3 pathway will elucidate the underlying mechanisms in response to oxidative/carbonyl stress, and will provide the possible therapeutic interventions in treatment of COPD based on SIRT1 activation.…”
mentioning
confidence: 99%
“…SIRT1 expression is decreased in the lung tissues from patients with COPD by oxidative stress and smoking [128] . Decreased SIRT1 expression results in the increased expression of proinflammatory cytokines due to NF-κB activation, and also results in the acceleration of cellular senescence mediated by the decrease of anti-senescent activity through FOXO3 [129] . Cellular senescence and emphysema were suppressed in SIRT1 transgenic mice by a FOXO3-mediated reduction of premature senescence in mice, while those are deteriorated in SITR1 knockout mice [130] .…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%